Ethnicity and Race Variations in Receipt of Surgery among Veterans with and without Depression. (12th October 2011) - Copeland, Laurel A.; Zeber, John E.; Pugh, Mary Jo; Phillips, Karon L.; Lawrence, Valerie A.
Abstract : To examine equity in one aspect of care provision in the Veterans Health Administration, this study analyzed factors associated with receipt of coronary artery bypass graft (CABG), vascular, hip/knee, or digestive system surgeries during FY2006–2009. A random sample of patients (N = 317, 072 ) included 9% with depression, 17% African-American patients, 5% Hispanics, and 5% women. In the four-year followup, 18, 334 patients (6%) experienced surgery: 3, 109 hip/knee, 3, 755 digestive, 1, 899 CABG, and 11, 330 vascular operations. Patients with preexisting depression were less likely to have surgery than nondepressed patients (4% versus 6%). In covariate-adjusted analyses, minority patients were slightly less likely to receive vascular operations compared to white patients (Hispanic OR = 0.88, P < .01 ; African-American OR = 0.93, P < .01 ) but more likely to undergo digestive system procedures. Some race-/ethnicity-related disparities of care for cardiovascular disease may persist for veterans using the VHA.